Business Feasibility Study: Electrifying Lifestyle to Optimize Working Capital Turnover and Revenue Enhancement at Koperasi PLN Babel - Warassih, Anggit Praharasty; Djatmiko, Budi (Economic: Journal Economic and Business, 2022)
Nowadays saving the planet from the climate crisis become a theme being campaigned around the world, including Indonesia. The implementation of the Electrifying Lifestyle encourages the transition of old appliances to more eco-friendly electrical appliances. This new all-electric lifestyle is a good business opportunity to develop. This research aims to conduct a feasibility study on the development plan of the Koperasi PLN Babel located in Pangkalpinang City, Bangka Belitung Islands Province. This research analyzes the existing internal and external conditions of Koperasi PLN Babel and evaluates from various aspects of the company, including aspects of business management, marketing, operations, human resources, and finance. The results showed that with innovation in all aspects analyzed it will perform results that are feasible to be realized in determining company policies for optimizing working capital turnover and revenue enhancement.